Traditional Chinese medicine and natural products in management of hepatocellular carcinoma: Biological mechanisms and therapeutic potential - Yunqing Xun; Guang Chen; Guoyi Tang; Cheng Zhang; Shichen Zhou; Tung-Leong Fong; Yue Chen; Ruogu Xiong; Ning Wang; Yibin Feng (Pharmacological Research)
Hepatocellular carcinoma (HCC), originating from hepatocytes, is the most common type of primary liver cancer. HCC imposes a significant global health burden with high morbidity and mortality, making it a critical public concern. Surgical interventions, including hepatectomy and liver transplantation, are pivotal in achieving long-term survival for patients with HCC. Additionally, ablation therapy, endovascular interventional therapy, radiotherapy, and systemic anti-tumor therapies are commonly employed. However, these treatment modalities are often associated with considerable challenges, including high postoperative recurrence rates and adverse effects. Traditional Chinese medicine (TCM) and natural products have been utilized for centuries as a complementary approach in managing HCC and its complications, demonstrating favorable clinical outcomes. Various bioactive compounds derived from TCM and natural products have been identified and purified, and their mechanisms of action have been extensively investigated. This review aims to provide a comprehensive and up-to-date evaluation of the clinical efficacy of TCM, natural products and their active constituents in the treatment and management of HCC. Particular emphasis is placed on elucidating the potential molecular mechanisms and therapeutic targets of these agents, including their roles in inhibiting HCC cell proliferation, inducing apoptosis and pyroptosis, suppressing tumor invasion and metastasis, and restraining angiogenesis within HCC tissues.